Pengaruh Strategi Promosi Terhadap Peningkatan Volume Penjualan Pada Cv Karya Abadi Simo Kwagean - Abdul Hamid; Moh. Ahyar Maarif (Fakultas Ekonomi dan Bisnis Islam, 2020)
Sales will not be realized without promotion, therefore CV Karya Abadi promotes Advertising and personalselling strategies to increase sales volume. This study aims to determine the promotion through advertising and personal selling affect sales volume in C.V. Eternal Work to achieve this goal the researcher first conducts a survey to identify what variables are considered. In this study there are three variables, namely sales volume, advertising and personal selling. The sample method used is porposive sampling (sampling technique with certain considerations). For the data obtained directly from research in CV Karya Abadi through un-structured interviews, observations and documentation and analyzed using the significance test of each coefficient and the significance test of the model through SPSS version 10.01. From the statistical results it can be seen that the value of Fcount> Ftable (76, 909> 3.3541) then the independent variables (advertising and personal selling) have a significant effect so H0 is rejected and H1 is accepted. For the T-test on advertising: 2,239 and personal selling: 11,104 and for Ttabel advertising and personal selling is +2,0518, this shows Thitung> Ttable so H1 is rejected and H0 is accepted. Thus it can be concluded that the promotion strategy (advertising and personal selling) affects the sales volume of C.V. Karya Abadi by 83.1% while 14.9% is influenced by other promotional strategies.